Pengaruh Waktu Proses Permesinan dari Penetapan Urutan Pahat Proses terhadap Sumbu z - Lobes Herdiman (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2003)
This paper will discuss about CNC turning machining process. One of the way to increase productivity in CNC machining process is by tooling process sequencing in processing workpiece feature. Tool sequencing in CNC turning machining process can be made by comparing tool sequencing process model 1 (turning3. SD1) with tool sequence process model 2 (turning1. SD1), these activity is needed to measure the distance effect from workpiece cutting process with tool in z axis. Comparison between model 1 and model 2 can be a guidance to achieve the optimum processing time. This paper is expected could explain how to increase processing time productivity by feeding tool sequence for cutting process. Another advantage from feeding tool sequence is the short cuting time that directly decrease maximum cutting (Flmax) and also unproper NC machining program.